prove that 2a=b+c, Mathematics

If the roots of the equation (a-b)x2 + (b-c) x+ (c - a)= 0 are equal. Prove that 2a=b+c.

Ans:    (a-b)x2 + (b-c) x+ (c - a) = 0

T.P 2a = b + c

B2 - 4AC = 0

(b-c)2 - [4(a-b) (c - a)] = 0

b2-2bc + c2 - [4(ac-a2 - bc + ab)] = 0

⇒ b2-2bc + c2 - 4ac + 4a2 + 4bc - 4ab = 0

⇒ b2+ 2bc + c2 + 4a2 - 4ac - 4ab= 0

⇒ (b + c - 2a)2 = 0

⇒ b + c  = 2a

 

Posted Date: 4/8/2013 5:05:51 AM | Location : United States







Related Discussions:- prove that 2a=b+c, Assignment Help, Ask Question on prove that 2a=b+c, Get Answer, Expert's Help, prove that 2a=b+c Discussions

Write discussion on prove that 2a=b+c
Your posts are moderated
Related Questions
I need help to understand: fxx for f(x,y)=x^2+y^2-2xy

I need help with my calculus

If 2/3 of a number is 24 then 1/4 of a number is...

Differentiate the following functions. (a) f (t ) = 4 cos -1 (t ) -10 tan -1 (t ) (b)  y = √z sin -1 ( z ) Solution (a) Not much to carry out with this one other

how you divide 100 by 10 and then x by 10

Q. How to Subtract fractions with different denominators? Ans. As with adding fractions, you can't subtract unless the denominators are the same. Here is an example: 9/

An unbiased die is tossed twice .Find the probability of getting a 4,5,6 on the first toss and a 1,2,3,4 on the second toss

solve the recurrence relation an=2an-1+n, a0=1


Can someone please help me grasp the concept of angles of depression and elevation?